2014
DOI: 10.1080/08856257.2014.986909
|View full text |Cite
|
Sign up to set email alerts
|

Quality of individualised education programme goals and objectives for preschool children with disabilities

Abstract: Individualised education programmes (IEPs) are the road maps for individualising services for children with disabilities, specifically through the development of high-quality child goals/objectives. High-quality IEP goals/objectives that are developed based on a comprehensive assessment of child functioning and directly connected to intervention and evaluation activities are more likely to support the individualisation of services and as a result, child development and learning. High-quality goals/objectives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 23 publications
1
30
0
13
Order By: Relevance
“…We argue that the fragmented structure of the EHC plan, which separates the three domains, contributes to this presentation; it is impossible in real life to separate education, health and social care domains, as they are constantly interacting to define the individual's functioning (World Health Organization, 2001;Rakap, 2015). Over the last 20 years, the WHO has endorsed a definition of "health status" that moves beyond the mere existence of medical issues, to include a "State of complete physical, mental, and social well-being, and not merely the absence of disease or infirmity" (.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We argue that the fragmented structure of the EHC plan, which separates the three domains, contributes to this presentation; it is impossible in real life to separate education, health and social care domains, as they are constantly interacting to define the individual's functioning (World Health Organization, 2001;Rakap, 2015). Over the last 20 years, the WHO has endorsed a definition of "health status" that moves beyond the mere existence of medical issues, to include a "State of complete physical, mental, and social well-being, and not merely the absence of disease or infirmity" (.…”
Section: Discussionmentioning
confidence: 99%
“…The match between these items and the SMART criteria proposed by the SEND Code of Practice for developing outcomes in the EHC plans is clear and has been extensively discussed elsewhere (Castro et al, 2019). The scale has also been used in similar studies with very high levels of interrater agreement (93% and above) (e.g., Boavida et al, 2010;Rakap, 2015).…”
Section: Instruments and Materialsmentioning
confidence: 99%
“…In previous research, the quality of the objectives in particular seems to have been studied thoroughly, and this is likely because their significance has been highlighted (e.g., Christle & Yell, 2010;Drasgow et al, 2001). However, in these studies, the objectives elaborated in pedagogical documents have been found to be generally poor in quality, especially concerning their measurability (Michinowicz at al., 1995;Rakap, 2015;Rubler, McGrew, Dalrymple, & Jung, 2010;Sanches-Ferreira, Lopes-dos-Santos, Alves, Santos, & Silveira-Maia, 2013). This is presumably because they were written in an imprecise and inadequate manner (Ruble et al, 2010;Sanches-Ferreira et al, 2013).…”
Section: Writing Pedagogical Documents: Current Practicesmentioning
confidence: 99%
“…Au-delà du Québec, plusieurs études mentionnent que la qualité des objectifs est faible (Rakap, 2015;Ruble, McGrew, Dalrymple, Lee et Jung, 2010;Sanches-Ferreira, Lopes-dos-Santos, Santos et Silveira-Maia, 2013). D'autres études démontrent que la qualité des PI/PT s'améliore après avoir suivi une formation (Krishnakumar, Greeta et Palat, 2006;Pretti-Frontczac et Bricker, 2000).…”
Section: Ce Que Les Recherches Disent à Propos De La Qualité Des Pi/ptunclassified
“…De plus, Spillane (1990) agrémente sa démarche d'évaluation en ajoutant les critères d'analyse suivants : le pourcentage de besoins d'apprentissage identifiés, les niveaux actuels de performance cités, le nombre de buts ou d'objectifs à long terme et à court terme, le nombre et la variation des moyens ainsi que la présence des services offerts. Plusieurs études ont d'ailleurs utilisé l'instrument de mesure appelé le Goal Functionality Scale II (Boavida et al, 2013;Boavida et al, 2010;Hamilton, 1995;Notari et Bricker, 1990;Pretti-Frontczac et Bricker, 2000;Rakap, 2015). Cet instrument cible : 1) l'adaptabilité (l'objectif vise l'intégration dans le quotidien); 2) la fonctionnalité (l'objectif favorise l'autonomie); 3) la transférabilité (l'objectif s'applique dans plusieurs contextes ou vise des concepts généraux); 4) la mesurabilité (l'objectif est mesurable à des fins d'évaluation); et 5) la relation hiérarchique entre les objectifs, soit : est-ce que l'objectif établit un lien logique et cohérent.…”
Section: Les Inventaires Ou Les Listes Gaudreau Et Ses Collaborateursunclassified